HOW TO IMPROVE WRITING ANG SPEAKING SKILLS - Odiljanova Shahzoda; Narimanova Jamola (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Today, listening and speaking skills have crucial role both in daily life and in academic events as it important for to keep productive communication. Despite that importance of listening and speaking skills in the development, did not start to take its place in language teaching sphere during decades.However, in recent years, listening and speaking strategies are also started developing in its language programs. In addition there are various of perspectives to improve listening and speaking skills which helps to minimise the listening comprehensions and speaking challenges experienced by language learners.This literature review aims to review the basic concepts related to importance of listening and speaking skills in learning English as foreign or second language, it mainly focused on listening comprehension and listening challenges which experienced by second and foreign learners.